How Can Burundi Raise its Growth Rate? : The Impact of Civil Conflicts and State Interventionon Burundi's Growth Performance - Basdevant, Olivier (Washington, D.C. : International Monetary Fund, 2009)
Over the last thirty years Burundi's low economic growth has led to a significant decline in per capita GDP. The purpose of this paper is to shed light on supply-side constraints that prevented Burundi's economy from growing faster. Lack of investment, civil conflict, economic inefficiencies, state intervention in the economy, and regulatory restrictions explain a large part of the weak growth performance for the last thirty years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet